Digital integrated circuit implementation of an identification stage for the detection of illegal hunting and logging - Salazar-García, Carlos; Alfaro-Hidalgo, Luis; Carvajal-Delgado, Mauricio; Montero-Aragón, Jordan; Castro-Gonzalez, Reinaldo; Agustín-Rodríguez, Juan; Chacón-Rodríguez, Alfonso; Alvarado-Moya, Pablo (Institute of Electrical and Electronics Engineers Inc., 2015)
Results of the VLSI implementation of an acoustic classification system's identification stage, intended for the detection of gunshots and chainsaws in a protected tropical area, are shown, with the idea of later building a surveillance wireless sensor network with similar nodes. The system performs from signal preprocessing to feature extraction, with results of the HDL description of the system tested on a FPGA against a golden reference, using real data taken from a protected rain forest area. Final classification of signals, using HMM, is in the final stages of testing. Some post-place-and-route results of the code ported to a commercial 130nm CMOS technology are also given.
https://www.scopus.com/inward/record.url?eid=2-s2.0-84945156734&partnerID=40&md5=314bbbafa852daae1ff0c96b8de9f2be
Keywords: ASIC; Circuitos; CMOS; FPGA; Protección del medio ambiente; Research Subject Categories::TECHNOLOGY::Information technology::Computer science::Software engineering